Detection of rhinovirus RNA in lower airway cells during experimentally induced infection - Gern, J E; Galagan, D M; Jarjour, N N; Dick, E C; Busse, W W (American journal of respiratory and critical care medicine, 1997)
Rhinovirus (RV) infections are presumed to be localized to the upper airway, yet can cause severe lower airway symptoms in children and adults with asthma. To test the hypothesis that rhinovirus infection of the upper airway may be associated with the presence of virus in lower airway cells, we used the techniques of reverse transcription-polymerase chain reaction (RT-PCR) and Southern blotting to detect RV RNA in lower airway cells from eight allergic volunteers experimentally infected with RV16. Bronchoscopy with bronchoalveolar lavage (BAL) was done 1 mo before, and 2 and 4 d after an experimental infection with RV16. All subjects developed cold symptoms, and infection was confirmed by culturing RV16 from nasal secretions. Rhinovirus RNA was detected in both nasal lavage and lower airway cells from all eight subjects 2 to 4 d after an experimental inoculation, but not in any of the precold specimens from either the nose or the lower airway. These findings suggest that RV can infect cells of the lower airway, and raise the possibility that such an effect can promote asthma exacerbations in the susceptible host through direct enhancement of local inflammation.